Otitis Externa in a Newborn After Waterbirth—A Case Report Followed by a Literature Review - Julia Ufnal; Maria Wolniewicz; Lidia Zawadzka-Głos (Journal of Clinical Medicine, 2026)
Waterbirth has become a widely adopted alternative to a conventional delivery, with well-documented maternal benefits, but there is an ongoing debate regarding neonatal safety. We would like to report a case of a 10-day-old male neonate who developed acute otitis externa (AOE) following waterbirth. Despite the rare occurrence of this disease in children under 2 years of age, prompt diagnosis and timely initiation of appropriate therapy led to a full recovery. This case represents a previously undocumented, yet plausible, complication of waterbirth and underscores the importance of careful neonatal ear assessment and preventive measures in aquatic deliveries.